Clinical Features and Prognosis According to Immunophenotypic Subtypes Including the Early T-Cell Precursor Subtype of T-Lymphoblastic Lymphoma in the Japanese Pediatric Leukemia/Lymphoma Study Group ALB-NHL03 Study. Issue 1 (January 2018) - Fukano, Reiji; Sunami, Shosuke; Sekimizu, Masahiro; Takimoto, Tetsuya; Mori, Tetsuya; Mitsui, Tetsuo; Mori, Takeshi; Saito, Akiko Moriya; Watanabe, Tomoyuki; Ohshima, Koichi; Fujimoto, Junichiro; Nakazawa, Atsuko; et al.
Abstract : We reviewed the immunophenotypic subtypes of pediatric T-cell lymphoblastic lymphoma in the Japanese Pediatric Leukemia/Lymphoma Study Group ALB-NHL03 study. Of the 104 patients, 40 patients each had sufficient data to evaluate the immunophenotypes and early T-cell precursor (ETP) subtype. Pro-T, pre-T, intermediate T, and mature T cells were observed in 1, 9, 21, and 9 cases, respectively. The 3-year event-free survival (EFS) rates of those with pro-T/pre-T, intermediate T, and mature T cells were 80.0±12.6%, 71.4±9.9%, and 88.9±10.5%, respectively ( P =0.546). There were 8 and 32 cases of ETP and non-ETP subtypes, with 3-year EFS rates of 75.0±15.3% and 71.9±8.0%, respectively ( P =0.828), indicating that the immunophenotypic subtype was not predictive of EFS in this study.